Benchmarking the estimation of optimal spatial resolution fro biodiversity studies on Ebro region data - Martinez, Emilce Soledad; Vilaprinyo, Ester; Asín, J.; Alves, Rui (Sociedad de Estadística e Investigación Operativa (España), 2025)
Poster